1987
DOI: 10.1007/bf00179928
|View full text |Cite
|
Sign up to set email alerts
|

The role of opioid receptors in diabetes and hyperglycemia-induced changes in pain threshold in the rat

Abstract: The role of opioid receptors in diabetes and hyperglycemia-induced analgesia was studied in male Sprague-Dawley rats. Animals maintained under controlled environmental conditions were used in all studies. Pain latency was determined by the hot plate test (55 degrees C) and analgesy-meter force method. The results of these studies indicate that streptozotocin-induced diabetic animals have a significantly higher pain threshold (P less than 0.01) than the control groups. The pain threshold was found to be diurnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
(13 reference statements)
1
13
1
Order By: Relevance
“…For example, genetically diabetic mice are shown to have increased reaction latencies to tail pinch and radiant heat (Levine et al 1982b). Similarly, in the hot plate test, streptozotocin-induced diabetic animals and dextrose-induced hyperglycemic animals were reported to show an elevation in pain threshold (Chu et al 1986;Akunne and Soliman 1987). In contrast, decreases in paw-lick and jump latencies have been reported in streptozotocin-treated rats (Forman et al 1986).…”
Section: Discussionmentioning
confidence: 94%
“…For example, genetically diabetic mice are shown to have increased reaction latencies to tail pinch and radiant heat (Levine et al 1982b). Similarly, in the hot plate test, streptozotocin-induced diabetic animals and dextrose-induced hyperglycemic animals were reported to show an elevation in pain threshold (Chu et al 1986;Akunne and Soliman 1987). In contrast, decreases in paw-lick and jump latencies have been reported in streptozotocin-treated rats (Forman et al 1986).…”
Section: Discussionmentioning
confidence: 94%
“…Duration of hyperglycemia, the severity of diabetic state, sex or species may affect progression to diabetic hyper-or hypoalgesia. While thermal hypoalgesia is reported in diabetic animals using tail-flick test or hot plate test [23][24][25], others have found hyperalgesia [26][27][28]. At 32 weeks of age, marked thermal hypoalgesia was observed in SDT rats by tail-flick test [17].…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…There are many studies of hyper and hypoalgesia in STZ-induced diabetic animal models. While thermal hypo-algesia is reported in diabetic rats using the tail-flick test or the hot-plate test [2,3,6,10,19,20] , others have found hyperalgesia in diabetic animals [13,31,37,38] . In the present study, alloxan-induced diabetic rats showed hyperalgesia in the formalin test and showed thermal hypoalgesia.…”
Section: Discussionmentioning
confidence: 99%